Why is economic geography an evolutionary science? - Ron Boschma; Koen Frenken (European Regional Science Association (ERSA), 2002)
During the past two decades, evolutionary economics has emerged as one of the innovative fields of research in economics, and in particular in the fields of the economics of technical change and theory of the firm (Nelson and Winter 1982; Dosi et al. 1988; Arthur 1994; Dosi et al. 2000). Parts of their subjects concern issues traditionally dealt with by economic geographers and regional scientists, including localised technological spill-overs, agglomeration economies, product life-cycle studies, international trade, spatial diffusion and regional policy. In some of these studies geography has been 'rediscovered', in particular those who are interested in uneven growth and development of regions and countries, and those who examine the role of proximity in technological innovation. In this paper, we aim to elaborate on a research programme for "evolutionary economic geography" following on a previous work (Boschma and Lambooy 1999). In short, the distinctive nature of such a programme lies in the integration of temporal (path-dependent) processes of economic change with spatial analysis of conditions and effects of such processes. For example, processes of structural change in economic regions are addressed as path-dependent and to a large extent irreversible economic processes that are enabled and constrained by technological and institutional networks that exist from the past (Boschma 1999). Similarly, the concept of national systems of innovation can be given an explicit evolutionary meaning when a national systems is modelled as an evolving complex system containing an interrelated set of institutions (Frenken 2000). It is further argued that the traditional research questions of economic geography and regional science remain pertinent, but that evolutionary economics provides a rich set of analytical and empirical tools to address these questions. Among these tools are: (i) simulation techniques from complexity studies that explicitly links micro-economic processes and macro-economic structures, (ii) empirical techniques that indicate the rate and nature of technical change, and historical studies that emphasise the role of "small events" in explaining long-run evolutionary specialisation patterns.
Keywords: 330